Educação e Tecnologia: o uso da multimídia na melhoria do ensino de literatura no CEFET-AL - Amaral, Valmir Pimentel (2005)
The aim of this paper is to analyze the application of the multimidia resources in the classroom, specially the computer as in improvement for the Literature teaching face to the pedagogical practice in CEFET-AL, and verify how the use of these new technologies means will contribute to the progress of this pedagogical action. For that, it uses as theoretical reference mainly the contributions of Pierre Lévy (that studies the new technologies and the changes of the world nowadays) emphasizing the new relation with knowledge due to these changes, besides authors working in Teaching and Literature fields, such as Nelly Novaes Coelho, Marisa Lajolo, Fortini, Afrânio Coutinho, among others. It is appropriate to point out the importance of Reading when doing literature, where both are inseparable and interdependent. The corpus was organized base don written questionnaires with closed and mixed questions to a total 0f 79 students of the three years of the Medium Level (equivalent to High School) of CEFET-AL, and also a recorded interview with four teachers of the Language Area of this Institution.